Carbonylation of alkynes, alkenes and alcohols using metal complex catalysts - Sarkar, B. R.; Chaudhari, Raghunath V. (Catalysis Surveys from Asia, 2005)
Carbonylation of olefins, alcohols and halides using homogeneous as well as heterogeneous catalysts has been discussed. Highlights of contributions on the activity, selectivity and stability of catalysts for carbonylation reactions are discussed. Kinetics and mechanism including characterization of the intermediate catalytic species has also been reviewed. The performance of anchored Pd complexes on mesoporous supports (MCM-41 and MCM-48), water soluble Pd complexes and supported Pd catalysts in carbonylation of aryl alcohols and olefins has been discussed in the context of catalyst-product separation. Some aspects of kinetic modelling and reaction engineering of these multiphase catalytic reactions have also been reviewed.
Keywords: Carbonylation; catalysis; Heterogenization; homogeneous; Palladium

Computational study of a single-phase flow in packed beds of spheres - Gunjal, P. R.; Ranade, V. V.; Chaudhari, Raghunath V. (AICHE Journal, 2005)
Packed-bed reactors are widely used in petrochemical, fine chemical, and pharmaceutical industries. Detailed knowledge of interstitial flow in the void space of such packed-bed reactors is essential for understanding the heat and mass transfer characteristics. In this paper, fluid flow through the array of spheres was studied using the unit-cell approach, in which different periodically repeating arrangements of particles such as simple cubical, 1-D rhombohedral, 3-D rhombohedral, and face-centered cubical geometries were considered. Single-phase flow through these geometries was simulated using computational fluid dynamics (CFD). The model was first validated by comparing predicted results with published experimental and computational results. The validated model was further used to study the effect of particle arrangement/orientation on velocity distribution and heat transfer characteristics. The simulated results were also used to understand and to quantify, relative contributions of surface drag and form drag in overall resistance to the flow through packed-bed reactors. The model and the results presented here would be useful in elucidating the role of microscopic flow structure on mixing and other transport processes occurring in packed-bed reactors. (C) 2005 American Institute of Chemical Engineers.
Keywords: CFD; drag; heat transfer; packed bed; packing arrangement

Catalytic asymmetric transfer hydrogenation of ketones using [Ru(p-cymene)Cl-2](2) with chiral amino alcohol ligands - Deshpande, Sudhindra H.; Kelkar, Ashutosh A.; Gonnade, Rajesh G.; Shingote, Savita K.; Chaudhari, Raghunath V. (Catalysis Letters, 2010)
Catalytic asymmetric transfer hydrogenation of aromatic alkyl ketones has been investigated using [Ru(p-cymene)Cl-2](2) and new derivatives of beta-amino alcohols synthesized from (S)-(-)-lactic acid and mandelic acid as ligands. Chiral secondary alcohols were obtained with good to excellent conversion (60-90%) and moderate to good enantioselectivities (40-86%). Asymmetric transfer hydrogenation of ketones has been investigated using [Ru(p-cymene)Cl-2](2) and beta-amino alcohols synthesized from (S)-(-)-lactic acid and Mandelic acid as ligands. Chiral secondary alcohols were obtained with good to excellent conversion (60-90%) and moderate to good enantioselectivities (40-86%).
Keywords: Amino alcohol ligand; Asymmetric transfer hydrogenation; Ketones; Ru catalyst